INOVASI CHEESE COOKIES GLUTEN FREE DENGAN COATING GULA PALM MENGGUNAKAN TEPUNG MOCAF DAN PATI GARUT - Yuliandari, Trianda; Ita Fatkhur Romadhoni; Any Sutiadiningsih; Mauren Gita Miranti (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research was conducted to develop an innovative gluten-free food product in the form of Cheese Cookie with palm sugar using mocaf flour and arrowroot starch as the main ingredients. The research was conducted through an experimental method with three different formulations, namely the ratio of mocaf flour and arrowroot starch of 50%:50%, 75%:25%, and 100%:0%, respectively. Organoleptic tests were carried out by 30 panelists, consisting of 25 semi-trained panelists and 5 trained panelists, who assessed the attributes of color, aroma, taste, texture, and level of preference. The test data were analyzed using a one-way ANOVA test and continued with a Duncan test to determine differences between treatments. The results of the analysis showed that there were no significant differences in sensory attributes between the three formulations. The best formulation was found to be the composition of 100% mocaf flour. These results indicate that Cheese Cookies dengan coating gula palm have the potential to be an alternative local gluten-free food product that is worthy of further development.